British Politics and Foreign Policy in the Age of Appeasement,1935-39 - Adams, R. author. aut Link
XII, 192 p.
Keywords: In this book historian R.J.Q. Adams examines the policy of appeasement as practiced by British Governments in the inter-war years - a programme widely praised in its day and frequently condemned as wrong-headed and even wicked ever since. In this thoroughly accessible work, he reveals the motivations and goals of the men who practiced appeasement as well as of those who opposed it, and makes clear the road to Munich - and to war.